Strawberries from integrated and organic production - Kristl, Janja (Acta chimica slovenica, 2013)
As the nutritional quality of food is becoming increasingly more important forconsumers, significant attention needs to be devoted to agricultural practices and their influences on the nutrient contents in food. The presentedinvestigation studied the mineral contents and antioxidant activitiesin the fruits of four organically-grown strawberry cultivars 'St. Pierre', 'Elsanta', 'Sugar Lia' and 'Thuchampion' when compared to those of integrated-grown plants. The strawberries were digested and analyzed for K, Mg, Fe, Zn, Cu, and Mn using an atomic absorption spectrometer, whilst P was analyzed using a vanadate-molybdate method. In addition, antioxidant activity was estimated by using the ABTS assay. The results showed that the mineral contents and antioxidant activities in strawberries depends on the cultivar, and its production system. Organically-grown fruits showed higher antioxidant activities and Cu content than the integrated fruits, whilst the integrated fruits were superior in their contents of P, K, Mg, Fe and Mn. All the cultivars showed similar Zn content, probably reflecting the fact that the Zn content in strawberries does not depend on the cultivar.
Keywords: analizna kemija; antioksidanti; antioxidant; antioxidant activity; ekološka proizvodnja; integrirana proizvodnja; jagode; minerals; production system; strawberries